Case Report: Experience in surgical management of vertebral posterior marginal osteophytes completely encasing the nerve root: a report of two cases - Li, Feng; Tan, Xingguo; Song, Mingjia; Zhang, Lian; Li, Songkai (Frontiers in Surgery, 2025)
Posterior marginal osteophytes at the vertebral level are frequently observed in individuals with lumbar disc herniation (LDH); however, complete encasement of the nerve root by such osteophytes is exceedingly uncommon. We present two cases of surgical management of vertebral posterior marginal osteophytes completely encasing the nerve root. This report examined two cases of LDH accompanied by vertebral posterior marginal osteophytes completely encasing the nerve roots. Both patients underwent spinal canal decompression, discectomy, and intervertebral fusion. Postoperatively, varying degrees of nerve root injury were noted. By the 3-month follow-up, marked recovery in neurological function was achieved in both cases. The presence of vertebral posterior marginal osteophytes completely encasing the nerve root represents a notable risk factor for nerve root injury in LDH cases. Tailored surgical approaches are imperative to minimize complications and optimize patient outcomes.